2014
DOI: 10.19173/irrodl.v15i3.1654
|View full text |Cite
|
Sign up to set email alerts
|

University faculty’s perspectives on the roles of e-instructors and their online instruction practice

Abstract: <p>Despite the rapid use of e-Learning in higher education, the beliefs of instructors about and their practices during online instruction have been seldom addressed. This study explores the role perceptions of e-instructors in higher education. In total, 106 instructors from 20 Taiwanese universities filled out a questionnaire. Analytical results indicate that “content expertise” and “instructional designer” are perceived by university faculty as the key components in e-instruction in higher education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 39 publications
2
47
0
5
Order By: Relevance
“…New Requirements for Tutors in the Educational Reform of China's Open Universities competencies of tutors in the e-learning environment will emerge (Berge, 1995;Shepherd, 2003;Denis et al, 2004;Darabi, Sikorski, & Harvey, 2006;Chang, Shen, & Liu, 2014). Specifically, three new roles for tutors in the Chinese learning context were found, namely the Instructional designer, Manager/Administrator, and Social roles, expected of Open University tutors in the e-learning environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New Requirements for Tutors in the Educational Reform of China's Open Universities competencies of tutors in the e-learning environment will emerge (Berge, 1995;Shepherd, 2003;Denis et al, 2004;Darabi, Sikorski, & Harvey, 2006;Chang, Shen, & Liu, 2014). Specifically, three new roles for tutors in the Chinese learning context were found, namely the Instructional designer, Manager/Administrator, and Social roles, expected of Open University tutors in the e-learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bawane and Spector (2009) rank the priority of pedagogy role (associated with the Instructor and Instructional designer roles in the present study) and the evaluator as first and third place among eight roles of the online instructor, respectively. Chang et al (2014) found that university faculty in Taiwan rank content expertise, instructional design, and learning assessment as having the three highest priorities among seven e-instructors' competencies. This finding reveals that tutors no longer provide merely cognitive support to students; rather, they are also involved in course design and development, which involvement in turn informs the fusion of course development and student support in open universities of China.…”
Section: The Priorities Of Tutor Roles and Competencies Compared Withmentioning
confidence: 98%
See 1 more Smart Citation
“…The traditional, classroom-based teaching is replaced by the technology-based teaching (Chang et al, 2014;Prestridge, 2012). This environment has created a co-operative learning and student-centred approach (Smeets et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The availability of online courses at tertiary education institutions (colleges and universities) increases dramatically over the last decade in many countries, including Australia (Chang, Shen, & Liu, 2014;Anderson, Johnson, & Saha, 2002). In Australia between the years 1980 and 2010 student enrolments in offcampus education increased steadily.…”
Section: Introductionmentioning
confidence: 99%